Reforma Agrária em questão: a propriedade privada como fator de desterritorialização camponesa no Assentamento Fazenda Primavera (Andradina-SP) - Santos, Rafael de Oliveira Coelho dos [UNESP] (2014)
The challenge of this research is to contribute with the debate which involves permanent land titles to families settled in the agrarian reform, exposing the territorial dispute between agribusiness and the peasantry seated in Settlement Project Fazenda Primavera, in Andradina, northwest of the state of São Paulo, where families are already own the land. This conjuncture is contained in the structural conflict between peasantry and agribusiness with its interpretive paradigms of agricultural reality, that reveals the State as a body crossed by contradictions which cannot be conceived as neutral in the class struggle, detached from the exploration or reproduction of social classes. The advance of agribusiness has shown the persistence of conflict and the contradiction in social relations that modify the configuration of the territories and update the Brazilian Agrarian Question. Agricultural revolutions, the monopolization of public policies and state funds, the unequal allocation of resources and the prospect of growth as synonymous of productivity, attributed to agribusiness hegemonic condition, excluding much of the peasantry of modern production circuits with their technological standards, which establish forms of resistance in the territory. We seek to identify how the factors that interfere in territorial disputes, like the emancipation of the settlements and the insufficiency of public policy, articulate and materialize in geographic processes such as deterritorialization. The expansion of sugar cane and eucalyptus indicates that the dispute is for access to the fundamental resources to productive activity, such as land and territory.